The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s42452-020-2227-0
|View full text |Cite
|
Sign up to set email alerts
|

Social vulnerability of smallholder farmers to climate change in Zambia: the applicability of social vulnerability index

Abstract: This study assesses social vulnerability and coping strategies of smallholder farmers in two districts in Zambia and the applicability of the social vulnerability index (SVI) approach. Household data from 194 households were collected for the assessment of vulnerability and coping strategies. Using six demographic, economic and social indicators, farmers in Chirundu district were found to be more vulnerable to climate change than those in Masaiti district having recorded SVI of 0.47 and 0.41, respectively. Eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Krell et al [32] stated that political considerations and weakness of the infrastructures are of the main limitations for adaptive responses of the farming communities against the climate change impacts. Similar findings have been reported by the researchers from other countries including Zambia [52] and Egypt [53]. To be specific, most of these studies suggest that, in order to provide easier and better meteorological information to farmers, first, inter-institutional cooperation between stakeholders should be increased.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Krell et al [32] stated that political considerations and weakness of the infrastructures are of the main limitations for adaptive responses of the farming communities against the climate change impacts. Similar findings have been reported by the researchers from other countries including Zambia [52] and Egypt [53]. To be specific, most of these studies suggest that, in order to provide easier and better meteorological information to farmers, first, inter-institutional cooperation between stakeholders should be increased.…”
Section: Discussionsupporting
confidence: 81%
“…The applicability of this recommendation has been supported by others. For instance, Dumenu and Tiamgne [52] concluded that information barriers are of the main factors resulting in the vulnerability of farming communities against climate change in Zambia. Similar results can be found among the results of the researchers from Brazil [26], Kenya [27,32], Vietnam [28], Nigeria [31], and Taiwan [33].…”
Section: Discussionmentioning
confidence: 99%
“…Internationally, emerging research is applying the SVI to natural and manmade disasters (flash flooding, climate change, etc. [ 19 , 20 , 21 , 22 ]) and other health outcomes [ 23 , 24 , 25 , 26 ]. The opioid epidemic can be considered a “man-made” disaster, as opioid-related deaths continue to increase, despite efforts to curtail this trend.…”
Section: Introductionmentioning
confidence: 99%
“…Others used both econometric and indicator-based methods. The econometric method uses household-level socioeconomic survey data [37], while the indicator-based method uses natural, social, financial, physical, and human capitals and then systematically combines to measure vulnerability status [21,24,28,[38][39][40][41][42][43]. The present study used an indicator-based approach, which is the most common method of demonstrating the power of each factor in vulnerability assessment [44][45].…”
Section: Introductionmentioning
confidence: 99%